METHODS FOR LONG - TERM LOCAL DEVELOPMENT PLANNING - Rajković, Biljana Lj.; Stojković, Aleksandra Lj; Rajković, Miloš D (Poslovna ekonomija, 2017)
SUMMARY: According to the modern theory of planning, by the long-term planning (of municipalities and cities) the foundations of the development of the concrete local community are set, since it is the base for the making of accompanying medium and short-term plans for the observed development. However, the current rapid development of science, technology and globalisation demands adequate methods of planning in the observed planning with the disorganised structure, and because of that in that field the results are not so good – which is especially applied to the less developed countries such as Serbia. The main goal of this work is to contribute to the scientific organisation of the method for long-term local development planning and so to make this very important type of planning more efficient.